PMCA2 pump mutations and hereditary deafness. (10th January 2018) - Bortolozzi, Mario; Mammano, Fabio
Highlights: The PMCA2 w/a pump extrudes Ca 2+ in the stereocilia of inner ear hair cells. PMCA2 mutations cause deafness and loss of balance in humans and mice. Reduced Ca 2+ extrusion by mutant PMCA2w/a affects hair cell mechanotransduction. Altered mechanotransduction correlates with loss of auditory function and hair cells. Abstract: Hair cells of the inner ear detect sound stimuli, inertial or gravitational forces by deflection of their apical stereocilia. A small number of stereociliary cation-selective mechanotransduction (MET) channels admit K + and Ca 2+ ions into the cytoplasm promoting hair cell membrane depolarization and, consequently, neurotransmitter release at the cell basolateral pole. Ca 2+ influx into the stereocilia compartment is counteracted by the unusual w / a splicing variant of plasma-membrane calcium-pump isoform 2 (PMCA2) which, unlike other PMCA2 variants, increases only marginally its activity in response to a rapid variation of the cytoplasmic free Ca 2+ concentration ([Ca 2+ ]c ). Missense mutations of PMCA2 w / a cause deafness and loss of balance in humans. Mouse models in which the pump is genetically ablated or mutated show hearing and balance impairment, which correlates with defects in homeostatic regulation of stereociliary [Ca 2+ ]c, decreased sensitivity of mechanotransduction channels to hair bundle displacement and progressive degeneration of the organ of Corti. These results highlight a critical role played by the PMCA2 w/a pump in the control of hair cell function and survival, and provide mechanistic insight into the etiology of deafness and vestibular disorders.